The greatest movie ever sold [videorecording (DVD)] - Spurlock, Morgan, 1970-; Spurlock, Morgan, 1970-; Berg, Peter, 1964-; Chomsky, Noam; Nader, Ralph (Sony Pictures Home Entertainment, 2011)
Morgan Spurlock brings a comedic documentary about branding, advertising, and product placement that is financed and made possible by brands, advertising, and product placement.